A Study of Indianness, Mythical Techniques, and Fictionalizations in the Novels of Raja Rao - Salmani, Naisima; Raza, Mohd Hamid (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2024)
This research paper represented the concept notes of the Indianness, mythical techniques, and fictionalizations related to the works of Raja Rao; an Indian English writer who enhanced the principles and parameters of the myth vs. reality. In this research paper, the researcher dignified the basic issues related to the socio-cultural activities and justified the ways of fictionalizations through the mythical approaches and techniques. The objective of this research paper is to focus on the significant parameters of the Indianness, Mythical Techniques, and Fictionalization in the novels of Raja Rao for the determination of the myth and reality related to the effective parameters of Gandhian Principles. In this research paper, it’s mentioned that the researcher collected the primary as well as secondary data through different sources and resources. The researcher investigated and explored the mythical techniques of Raja Rao to assume the background of the characters used in the novels as ‘Kanthapura’ and ‘The Serpent and the Rope.’ In this research paper, the researcher also represented the mythical approaches of Raja Rao to signify the collaboration and co-operation of the characters for the observation of the Gandhian principles implemented to get the liberty, equality, and fraternity. Apart from it, the researcher visited the various institutes for the collection of the texts to analyze the fictions of Raja Rao and other Indian English writers for the implementation of the Indianness and socio-cultural practices.